Fluid medium effect on stresses in suspensions of high-inertia rod-like particles. (August 2019) - Mahajan, Vinay V.; Mehmood, Junaid; El Hasadi, Yousef M.F.; Padding, Johan T.
Graphical abstract: Highlights: Investigated Couette flow of inertial rod-like particles via CFD-DEM simulations. Effect of particle shape on measured shear stresses is substantial. Rods in air show stress scaling similar to dry granular flow, but with altered values. Rods in water show different stress scaling than in air or dry. Rod-like particles under shear flow show strong tendency to shear alignment. Abstract: The rheology of suspensions of high-inertia (or granular) non-spherical particles characterized by high particle Stokes and Reynolds numbers is rarely investigated. In this study, we investigate the rheology of suspensions of inertial rod-like particles of aspect ratio 4 subjected to shear flow. In particular, the effect of fluid medium (air, water) against dry granular simulations on the developed stresses is assessed. CFD-DEM simulations are performed for a periodic shear box for a range of shear rates and volume fractions of particles. The dependence of rheological properties like shear stress, normal stress difference, pressure and relative viscosity on volume fraction, shear rate, granular temperature and the particle orientation are discussed. These results provide insight into the macroscopic rheology of suspensions of rods and demonstrate that the effect of particle shape and surrounding fluid cannot be completely ignored. Air as a fluid medium shows similar scaling as compared to dry granular simulations, but the stress values are generally lower. We observe drastic change in both scaling and values for water as fluid medium. In all cases, the rods show strong alignment in the direction of shear. This study can be further extended to develop stress closures for use in Eulerian flow models.